Resonance study: effect of partial triples excitation using complex absorbing potential-based Fock-space multi-reference coupled cluster - Jana, Irina; Basumallick, Suhita; Pal, Sourav; Vaval, Nayana (International Journal of Quantum Chemistry, 2021)
Resonances are metastable states with finite lifetime. They play important role in physics, chemistry and biology. The theoretical calculation of resonance state is a challenging problem. In this paper we have studied the shape resonance of Be, Mg, N-2 and CO. We have used correlated independent particle approximation to the Fock space multi-reference coupled cluster singles-doubles with third-order triples (CAP-CIP-FSMRCCSD(T)) method augmented by complex absorption potential. The resonance energy and decay widths are obtained by solving a non-Hermitian eigen-value problem within FSMRCC framework. The effects of the lowest order triples on the resonance energy and decay are studied.
Keywords: complex absorbing potential; electron affinity; Fock‐ negative ion resonance; partial triples; space MRCC